Effect of ageing time in vacuum package on veal longissimus dorsi and biceps femoris physical and sensory traits - G. Baldi; S. Ratti; C.E.M. Bernardi; V. Dell'Orto; C. Corino; R. Compiani; C.A. Sgoifo Rossi (Chiriotti Editori, 2015)
Study evaluated the effects of vacuum ageing (2, 4, 6, 8, 10, 12, 16 days) on veal loin (longissimus dorsi; LD) and silverside (biceps femoris; BF) physical and sensory characteristics. Ageing did not affect cooking loss, increased LD pH and L*, a* and b* in both muscles. Shear force (SF) decreased until day 6 in LD and day 10 in BF. Aroma, flavor and taste were not affected, while texture traits were improved. SF was negative correlated with tenderness and juiciness and positive correlated with BF fibrousness and stringy sensation. Ageing improved texture properties without altering other sensory traits.